Supercritical Fluid Extraction of Berry Seeds: Chemical Composition and Antioxidant Activity - Graziele Gustinelli; Lovisa Eliasson; Cecilia Svelander; Thomas Andlid; Leif Lundin; Lilia Ahrné; Marie Alminger (Journal of Food Quality)
The influence of supercritical fluid extraction (SFE) and solvent extraction of oils from cloudberry, bilberry, and black currant seeds on the yield, chemical properties, and recovery of antioxidant compounds was investigated. SFE was performed for 1 h at 350 bar and at 50°C and 80°C. Fatty acids, vitamin E, carotenoids, and free radical-scavenging activity (DPPH) were assayed. SFE at 80°C resulted in higher oil yields for cloudberry and black currant seeds. The oils were rich in polyunsaturated fatty acids (PUFAs) (66.8%–75.9% w/w), with high percentages of linoleic and α-linolenic acids. The black currant seed extracts had the highest concentrations of vitamin E (range, 113.0–241.8 mg/100 g oil) and carotenoids (range, 11.5–32.3 mg/100 g oil) and the highest antioxidant activity. The cloudberry seed oils also had high antioxidant content and activity. These findings indicate the potential of SFE for the recovery of PUFA and antioxidant compounds in berry by-products.